Impact of Japanese GLO launch on Philip Morris International stock prices - Mitrová, Martina (2018)
The thesis deals with newly expanding segment of tobacco industry – “heat-not-burn” products in context of the current tobacco market and regulations. Heated tobacco products promise up to 90% risk reduction in using nicotine thanks to heating tobacco instead of burning it. The first product of this kind, iQOS by Philip Morris International (PMI), found a potentially strong rival in GLO launched by British American Tobacco, which impacted the Philip Morris International’s prices significantly since the day of the GLO launch announcement for Japanese market. The thesis aims to quantify the financial impact the shareholders of PMI suffered purely because of this by using “event study” methodology to detect abnormal losses.